A controladoria em instituições financeiras: estudo de caso no Banco do Nordeste do Brasil S.A. - Lima, Fernando Barros de (2008)
The Globalization, cultural and economical integration of the most different market types in the world, it has been inserting the financial institutions and the companies in general in an atmosphere highly competitive and complex, reinforcing the need that organizational structure, products and processes to contribute to the business efficaciousness and the continuity of the organization. In this context, the controllership, like organizational unit, and the other departments of the company, have to auxiliary to the managers of the organization in the obtaining of the business efficaciousness and in the execution of the institutional mission of the company. In that way, this work has as central objectives to identify the functions of the controllership department in the institution and verify that forms that functions are being noticed by the managers of the organization, because these managers are the main users of the instruments and products made available by that department.To reach the objectives of this work, it took place a research of descriptive character, through a case study in the Banco do Nordeste do Brasil S.A., being used the interview techniques, to identify the functions of the controllership department in the institution, and of questionnaire application, to verify the managers' perception regarding that functions. As a result of the research it was ended that the functions of the controllership, defined in the literature, are ample, complex and, due to that, they are accomplished, not just for the controllership department, but also for other departments that compose the structure of the institution. It was outstanding also that the controllership unit possesses important function in the integration and in the obtaining of the results of the other departments, in the decision-making process of the institution and in the obtaining of the efficaciousness of the company.